Sistemas informático de monitoreo y control de variables hidrográficas de la Micro-Cuenca del Río Cutuchi - Analuisa Toro, Stalin Vladimir (2017)
Organizations today try to improve their processes using different means, such as computer tools. The present technological proposal recommends to improve the process of data management in the Ecuadorian Central of Agricultural Services (CESA) which manually handled the data registration using a program called HOBOware, which presented problems in the moment of rendering accounts or to make the daily reports. The main objective is the development of a web application that facilitates the process of data management, taking account aspects such as: management of the documentation required to save the acquired data and to reflect them by means of graphs to carry out a monitoring of obtained variables, user account management, storage of all data entered, dynamic content management and multiple reports. As a procedure, we chose to use the agile SCRUM methodology which allows for the proper organization of work throughout the development cycle. To achieve this, we have defined the use of the PHP programming language, this language is oriented to the fastest development of web applications for which it uses a modern software architecture since it uses Model Vista Controller, in order to get a better user experience is used jQuery technologies, finally as storage medium was considered the use of the MySql database engine. The main results were successful, because when the pilot test was performed it worked properly which recorded all the data and when consulting the daily reports, is reflected according to the years by means of graphs for a greater visualization of information for the user